Efficacy of Cover Crops on Weed Suppression, Wheat Yield, and Water Conservation in Winter Wheat–Sorghum–Fallow. Issue 4 (1st July 2019) - Mesbah, Abdel; Nilahyane, Abdelaziz; Ghimire, Binod; Beck, Leslie; Ghimire, Rajan
ABSTRACT: Reducing the fallow period by using cover crops in a winter wheat ( Triticum aestivum L.)–sorghum [ Sorghum bicolor (L.) Moench]–fallow system has the potential to suppress weeds and improve wheat yield, yet limited information is available from the semiarid southern Great Plains (SGP) of the United States. This study determines the effects of spring‐planted cover crops on weed suppression and winter wheat yields in semiarid environments. The study used a randomized complete block design with eight cover crop treatments and three replications. The cover crop treatments consisted of fallow (weeds controlled with herbicide), pea ( Pisum sativum L.), oat ( Avena sativa L.), canola ( Brassica napus L.), pea + oat, pea + canola, pea + oat + canola, and six‐species mixture of pea + oat + canola + hairy vetch ( Vicia villosa L.) + forage radish ( Raphanus sativus L.) + barley ( Hordeum vulgare L.). Both winter wheat and cover crops received supplemental irrigation. The cover crops showed potential to suppress weeds and maintain good ground cover during summer. Specifically, weed biomass in the oat and oat mixtures with legumes and brassicas were 73 to 85% less than in fallow during 2018. Cover crops showed little effect on wheat yield, yield components, and water use efficiency. Although long‐term studies of cover crops effects on multiple ecosystem services may help to select the most effective cover crop on wheat yield and water use efficiency in the SGP, this study revealed benefit of cover cropping through weed suppression.